2021
DOI: 10.12750/jarb.36.4.299
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mito-TEMPO on the survival of vitrified bovine blastocysts in vitro

Abstract: Cryopreservation as a technique for reproduction is used to preserve the genetic complements on domestic animals and humans (Lee et al., 2014;Kim et al., 2020).Especially, cryopreservation technology provides ad-ditional opportunity of pregnancy through the vitrifiedwarmed process in animal embryos. This is applied as a necessary technique for pregnancy using in vitro fertilization (IVF) embryos to solve the difficulty of female infertility (Hara et al., 2018). However, cryopreservation method is accompanied b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…These results are in concordance with those reported by Mehaisen et al (2015), where melatonin supplements promoted improved development of both the fresh and vitrified rabbit embryos through antioxidant capacity. Moreover, our previous study similarly indicated that supplementation of Mito-TEMPO during cryopreservation could protect the apoptosis-related ROS and mitochondrial superoxide, which occurred through mitochondrial activation and improved the developmental competence of the freezethawed blastocysts (Jeong et al, 2021). The embryos that survived following their freezing exhibited defects such as a disruption in the cytoskeleton structure and stabilization, high levels of ROS production, and oxidative stress following vitrification (García-Martínez et al, 2020).…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…These results are in concordance with those reported by Mehaisen et al (2015), where melatonin supplements promoted improved development of both the fresh and vitrified rabbit embryos through antioxidant capacity. Moreover, our previous study similarly indicated that supplementation of Mito-TEMPO during cryopreservation could protect the apoptosis-related ROS and mitochondrial superoxide, which occurred through mitochondrial activation and improved the developmental competence of the freezethawed blastocysts (Jeong et al, 2021). The embryos that survived following their freezing exhibited defects such as a disruption in the cytoskeleton structure and stabilization, high levels of ROS production, and oxidative stress following vitrification (García-Martínez et al, 2020).…”
Section: Discussionmentioning
confidence: 91%
“…Previous studies mainly discussed the antioxidative effects on the morphological variations regarding the in vitro embryo development and vitrification embryos, such as cleavage rate, blastocyst rate, expanded blastocyst rate, the total blastocyst cell numbers, and the survival rate following the freeze-thawing process (Jeong et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations